Recurrence with pagetoid spread arising 17 years after surgery for intramucosal rectal cancer: a case report - Taichi Matsubara; Yuta Kasagi; Kippei Ogaki; Yu Nakaji; Ryota Nakanishi; Yuichiro Nakashima; Masahiko Sugiyama; Hideto Sonoda; Hiroshi Saeki; Eiji Oki; Yoshihiko Maehara (Surgical Case Reports, 2017)
Abstract Background Perianal Paget’s disease (pPD) is uncommon, with only about 180 cases documented in the literature. Anorectal carcinoma with pagetoid spread is even rarer. Case presentation An 81-year-old woman underwent rectal cancer extirpation with a transanal approach 17 years prior. She has since undergone two reoperations for local rectal cancer recurrence. Then, warts frequently appeared on the vulva on several occasions. Warts appeared on the vulva 1 year ago, which were diagnosed as pPD by biopsy. She underwent perineal tumor resection, and the final histological diagnosis was rectal cancer recurrence with pagetoid spread. The resected stump was positive for cancer cells, and tumor progression was rapid. She underwent additional abdominoperineal resection (Miles’ operation) with lymph node dissection. However, disease progression was rapid and she died 7 months after the Miles’ operation. Conclusions There are some case reports describing anorectal carcinoma with pagetoid spread, however, almost of all those cases were synchronous primary anorectal cancer. Here, we report the first case of metachronous recurrence rectal cancer with pagetoid spread arising 17 years after surgery.